Implementation Of The Rivest Cipher 4 Method Web-Based Employee Data - Dwi Kuswanto; Ach. Khozaimi; Deden Nur Eka Abdi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Data security has always been an exciting topic to discuss in the era of globalization and industrial revolution 5.0. Along with the development of Cryptographic techniques, which continue to develop. Security of data storage techniques is essential in a data security system. The method used in this research is the Rivest Chiper 4 Algorithm. This research takes a case study of employee data storage security in a company that uses local storage as a medium for storing employee data. A web-based employee data collection system with the Rivest Chiper 4 algorithm implemented on the server side. The research results show that in testing the Avalanche Effect Rivest Chiper 4 algorithm with three key character length variations, an average value of 50.87% was obtained. The test results show that the average Avalanche Effect value is more than 50%, indicating that small changes to the plaintext can impact the ciphertext. With the help of Cryptool 1, using Brute Force time testing results with variations in key length, the password cracking time was 33 years with a 6-character key length. The longer the key is used, the longer the completion process will take to crack the ciphertext. Meanwhile, plaintext length is linearly correlated with the length of Brute Force testing time but is insignificant. Hardware performance also affects the estimated time of Brute Force.